2014
DOI: 10.5152/tjbh.2014.1773
|View full text |Cite
|
Sign up to set email alerts
|

Survival Analysis of Triple Negative and Her2 Positive Breast Cancer Patients: Single Center Report

Abstract: Objective: Triple negative and human epidermal growth factor receptor 2 (Her2) positive breast tumors are characterized by the absence of expression of estrogen and progesterone receptors and with either Her2 expression or not. Generally, they are larger tumors with higher grade, higher incidence of recurrence and distant metastasis. This article will investigate clinical, pathological, and molecular features of these high risk breast cancer patients and whether these features are correlated with recurrences o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2014
2014
2014
2014

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 19 publications
1
0
0
Order By: Relevance
“…In addition data from a single institution series including some of the patients that constitutes a fraction of the patient group in this study; have reported a 5-year survival rate of 82.4% which was comparable to other hormone receptor negative disease when adjusted for known clinical factors such as age, stage, grade and nodal status (16). A recently published article from a single center in Turkey which included early triple-negative breast cancer patients also revealed a 81% five-year overall survival rate which was in concordance with our results (17 at similar DFS rates for both patient groups (18). Median overall survival rates could not be obtained but the 5-year DFS rates for TNBC and HER-2 positive patients were reported to be 67% and 66%, respectively which were slightly lower than our results.…”
Section: Resultssupporting
confidence: 91%
“…In addition data from a single institution series including some of the patients that constitutes a fraction of the patient group in this study; have reported a 5-year survival rate of 82.4% which was comparable to other hormone receptor negative disease when adjusted for known clinical factors such as age, stage, grade and nodal status (16). A recently published article from a single center in Turkey which included early triple-negative breast cancer patients also revealed a 81% five-year overall survival rate which was in concordance with our results (17 at similar DFS rates for both patient groups (18). Median overall survival rates could not be obtained but the 5-year DFS rates for TNBC and HER-2 positive patients were reported to be 67% and 66%, respectively which were slightly lower than our results.…”
Section: Resultssupporting
confidence: 91%